Pollination strategy of Gennaria diphylla (Orchidaceae) on the Canary Islands and on Madeira - Claessens, Jean; Aguiar, Antonio Franquinho; Karsholt, Ole; Bacallado, Juan José; Heijungs, Reinout; Gravendeel, Barbara (Mediterranean Botany, 2022)
Gennaria diphylla (Link) Parl. is a terrestrial, inconspicuous green orchid. Its distribution includes the central and western Mediterranean region as well as the Canary Islands and Madeira. Investigations on its pollination biology are scarce. In literature there are mentions of autogamy and of allogamy. Pollination and pollen import and export were studied on Tenerife and Madeira. The investigations showed autogamy plays a less important role than thought, although a caging experiment showed that the species is well capable of self-pollination. The orchid is pollinated by a variety of small moths, especially of the families Geometridae, Pyralidae and Crambidae. It is flowering in a period when few other plants flower, so there is little competition for pollinators. Complemented by autogamy this seems to be a successful strategy, as the species shows a relatively high average fruit set of 73 %.
Keywords: allogamy; autogamy; Gennaria diphylla; Orchidaceae; Madeira; Tenerife